Fenomena Urbanisasi: Transformasi spasial di Kawasan Pinggiran Kabupaten Sidoarjo - Siti Nuurlaily Rukmana; Moch Shofwan (Diponegoro University, 2020)
The phenomenon of urban transformation also occurs in Sidoarjo Regency which is located around the city of Surabaya. Its evidence is the expansion of built up area in several districts like Krian district. The aims of this resech are analyzing the spatial transformation in term of land use change and evaluating the percentage of land use that it is accordance with spatial document policy. The analysis technique use Geogrphical Information System and Remote Sensing then proceed with descriptive evaluative. The result of this research can be seen that the transformation of built up area since 1995-2018 is 5,23% while those that are not accordance with spatial documen are 7,63%.